‘[t]he Vessel containing the Sacred oyle’: Negotiating Kingship in the Scottish Coronation of Charles I - Lucy Dean (Royal Studies Journal)
Taking place over seven years after Charles I’s accession to the throne in 1625, his Scottish coronation was the topic of much contemporary discussion until its eventual fruition in 1633. This resulted in several prescriptive orders of ceremony being penned, plus various accounts of the actual event (including one by the Lyon King of Arms, James Balfour, who was master of ceremonies), a range of financial records and privy council communications with Whitehall and the English establishment. There was also a renewed interest in the royal robes and the honours – or regalia – in addition to the creation of an ampulla to carry the anointing oil. While Charles’s progress to Scotland, royal entry and coronation in Scotland have received attention in recent scholarship – including work by Dougal Shaw, Siobhan Keenan and Giovanna Guidicini – the ampulla is still something of an enigma. This study incorporates material culture and sensory analysis methodologies to put this object at the centre of an analysis of the Scottish coronation of Charles I. In doing so, it works to tease out more of the nuances and complexities at work in the ritual negotiations between an absentee king with determined policies around ritualised performance and an increasingly distanced and suspicious Scottish population.